The interaction mechanism of dolomite mineral and phosphoric acid and its impact on the Ti alloy corrosion - Inna V. Filippova; Amany M. Fekry; Shymaa S. Medany; Lev O. Filippov (Scientific Reports)
Abstract The interaction mechanism of dolomite rock mineral as a novel corrosion inhibitor for titanium alloy in phosphoric acid (0.001–0.5 M) has been investigated for the first time using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization measurements. Unlike prior studies on synthetic inhibitors, this work uniquely highlights the potential of a naturally abundant, eco-friendly mineral for corrosion mitigation. EIS results reveal a distinctive shift in the inhibition mechanism—from adsorption to diffusion-controlled processes—with increasing phosphoric acid concentration, corroborated by in-situ Raman spectroscopy. This is the first report showing that dolomite effectively reduces the corrosion rate of titanium alloy by forming a stable passive film, with optimal performance observed in low acid concentrations (0.001–0.01 M). Furthermore, at higher acid concentrations (0.1–0.5 M), the mechanism transition influences the film performance. Surface characterization using SEM, EDS, FTIR, XRD, XRF, and in-situ Raman spectroscopy confirms the protective film formation and elucidates the interaction chemistry. The study establishes dolomite as a sustainable alternative to synthetic inhibitors, offering new insights into corrosion protection strategies for titanium alloys.